2006
DOI: 10.1002/elan.200603623
|View full text |Cite
|
Sign up to set email alerts
|

QCM Immunosensor Based on Polyamidoamine Dendrimers

Abstract: The poly(amidoamine)(PAMAM) dendrimers of fourth generation (G4) and 1-hexadecanethiol (HDT) has been used for formation of self assembled monolayers on a gold surface for preparation of quartz crystal microbalance (QCM) immunosensor for detection of human IgG. The anti-IgG antibodies were immobilized on a surface of G4-HDT layers or those covered by Protein A. In later case the oriented immobilization of anti-IgG takes place due to preferred interaction of F c portion of antibodies with the Protein A. The det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In this work we analyzed freshly prepared biosensors. In principle regeneration of aptasensor is possible using high ionic strength (2 M NaCl) [31][32][33], while for antibodies, 0.1 M glycine-HCl may be used [34]. However, success in regeneration depends also on the supporting layers and on the method of immobilisation of biopolymers.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we analyzed freshly prepared biosensors. In principle regeneration of aptasensor is possible using high ionic strength (2 M NaCl) [31][32][33], while for antibodies, 0.1 M glycine-HCl may be used [34]. However, success in regeneration depends also on the supporting layers and on the method of immobilisation of biopolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Although the detection limit was similar in the two cases, the advantage of the aptasensor was its possibility of surface regeneration, which was impossible for an antigen-based biosensor. However, recently it has been shown that immobilization of anti-IgE on the dendrimer surface also allows us to regenerate an immunosensor (Svobodová et al, 2006). The QCM method was recently compared with the electrochemical biosensor assay of thrombin detection .…”
Section: Acoustic Methodsmentioning
confidence: 99%
“…The acoustic sensor was prepared as follows. The 8 MHz AT-cut quartz crystal (CH Instruments, USA) was first cleaned as reported previously [19] and then incorporated into a flow through system. The cell was previously described in detail [20].…”
Section: Determination Of Interaction Of the Antibodies Withmentioning
confidence: 99%